Morphological diversity of the Caspian Asp, Leuciscus aspius, in the South Caspian Sea basin (Osteichthyes: Cyprinidae). Issue 1 (2nd January 2021) - Abbasi, Keyvan; Mouludi-Saleh, Atta; Eagderi, Soheil
Abstract : To study the intraspecific diversity of the Caspian Asp, Leuciscus aspius in the South Caspian Sea region, Iran, we collected in 2016–2017 a total of 101 specimens from Aras River and Astara, Anzali, Kiashahr and Langeroud shores, and analysed 41 morphometric and nine meristic characteristics with multivariate statistical methods. Significant differences were found between these populations in 27 morphometric traits. A Principal Component Analysis (PCA) showed that the upper caudal-fin length and the maximum body depth are effective characters along the PC1 and PC2 axis, and based on MONOVA/CVA, the differences between the studied populations are significant (P<0.01). Morphometric characters were more powerful than meristic characters in distinguishing L. aspius populations. It is discussed whether differences in habitats and spawning grounds affect morphological traits.